Evaluation of accuracy of elastography point quantification versus other noninvasive modalities in staging of fibrosis in chronic hepatitis C virus patients. Issue 8 (August 2018) - Fouad, Rabab; Elbaz, Tamer; Abdel Alem, Shereen; Elsharkawy, Aisha; Negm, Mohamed; Khairy, Marwa; Hassany, Mohamed; Cordie, Ahmed; El Akel, Wafaa; Esmat, Gamal
Abstract : Background: Elastography point quantification (ElastPQ) is a newly noninvasive method incorporated into a conventional ultrasound system for staging of liver fibrosis in patients with chronic liver diseases. Aim: The aim was to evaluate ElastPQ reproducibility and its accuracy in staging of liver fibrosis in hepatitis C virus (HCV) patients in comparison with transient elastography (TE) and fibrosis scores [FIB-4 and aspartate aminotransferase-to-platelet ratio index (APRI)] using liver biopsy as a reference standard and also to predict the sensitivity and specificity of ElastPQ as well as proposing a cut-off for advanced fibrosis. Patients and methods: A single-center, cross-sectional study enrolled 72 chronic HCV patients. Baseline demographic and laboratory data were recorded. ElastPQ and TE were performed. Fibrosis scores were calculated. The performance of ElastPQ was compared with that of TE and noninvasive methods (FIB-4, APRI) using liver biopsy as a reference standard using receiver operating characteristic curve analysis. Results: ElastPQ is a valuable diagnostic tool for the diagnosis of F≥1, F≥2, and F≥3, with area under the receiver operating characteristic curve of 0.79, 0.74, and 0.83, respectively. The best cut-off values for ElastPQ were 4.9, 6.6, and 10.7 kPa for mild fibrosis, significant fibrosis, and advanced fibrosis, respectively. ElastPQ correlated positively with all other fibrosis indices (TE, APRI, and FIB-4) as well as liver biopsy. Area under the curve for the diagnosis of advanced fibrosis (F3/F4) using ElastPQ was 0.83 at a cut-off value of 10.7 kPa ( P <0.01). Conclusion: ElastPQ is a promising noninvasive US-based method for assessing liver fibrosis in HCV-related chronic liver disease patients with good diagnostic performance comparable to that of liver biopsy and TE.